ZOOMICS: Comparative Metabolomics of Red Blood Cells From Old World Monkeys and Humans - Bertolone, Lorenzo; Shin, Hye K.; Stefanoni, Davide; Baek, Jin Hyen; Gao, Yamei; Morrison, Evan J.; Nemkov, Travis; Thomas, Tiffany; Francis, Richard O.; Hod, Eldad A.; Zimring, James C.; Yoshida, Tatsuro; et al. (Frontiers in Physiology, 2020)
As part of the ZOOMICS project, we set out to investigate common and diverging metabolic traits in the blood metabolome across various species by taking advantage of recent developments in high-throughput metabolomics. Here we provide the first comparative metabolomics analysis of fresh and stored human (n=21, 10 male, 11 female), olive baboon (n=20), and rhesus macaque (n=20) red blood cells at baseline and upon 42 days of storage under blood bank conditions. The results indicated similarities and differences across species, which ultimately resulted in a differential propensity to undergo morphological alterations and lyse as a function of the duration of refrigerated storage. Focusing on purine oxidation, carboxylic acid, fatty acid, and arginine metabolism further highlighted species-specific metabolic wiring. For example, through a combination of steady state measurements and 13C615N4-arginine tracing experiments, we report an increase in arginine catabolism into ornithine in humans, suggestive of species-specific arginase 1 activity and nitric oxide synthesis – an observation that may impact the translatability of cardiovascular disease studies carried out in non-human primates. Finally, we correlated metabolic measurements to storage-induced morphological alterations via scanning electron microscopy and hemolysis, which were significantly lower in human red cells compared to both non-human primates.